FOSS4G 2010, un successo annunciato - GFOSS.it, GFOSS.it (GEOmedia, 2010)
A report from FOSS4G 2010 On September 6th to 9th was held in Barcelona FOSS4G Conference. FOSS4G is the symbol that identifies the area in Geospatial Open Source Software. This year the conference was organized in Europe, four years after the event in Lausanne (OSGeo typically try to alternate the conference between the various continents), after the event in previous years was held in Victoria (Canada), Sydney (Australia) and Cape Town (Africa).